Green Marketing Strategies for Sustainable Upcycling MSMEs in Bekasi Regency - Mulfi Sandi Yuda; Mochamad Afrizal Maulana; Yoki Muchsam; Galih Raspati (International Journal of Multidisciplinary Sciences and Arts, 2026)
The implementation of green marketing practices is a strategic necessity for Micro, Small, and Medium Enterprises (MSMEs) in facing the transition to a green economy as directed in the 2025–2029 National Medium-Term Development Plan (RPJMN). This transformation requires MSMEs to adapt through environmentally friendly product innovation, resource efficiency, and compliance with sustainability standards increasingly expected by modern consumers. However, conditions in Bekasi Regency show that most MSMEs based on industrial waste upcycling do not yet have a structured green marketing strategy and are unable to integrate sustainability principles into their business models. This challenge is exacerbated by low business understanding of green consumer behavior, minimal use of social media as a means of sustainability communication, and the lack of strategic guidelines tailored to local characteristics. This study aims to develop and validate a Green Marketing Strategy Model capable of optimizing the business sustainability of MSMEs in economic, social, and environmental dimensions. The research employed a qualitative approach using the Delphi Method involving academics, green MSME practitioners, local government, and environmental organizations. The Delphi process was conducted through several rounds to reach consensus regarding green marketing indicators and sustainability strategy priorities. The results produced a strategic model consisting of green marketing components, triple bottom line-based sustainability indicators, and digital marketing communication strategies relevant to local consumer characteristics. The study also provides practical recommendations for strengthening sustainable MSME development in Bekasi Regency and contributes theoretically to sustainability marketing practices in industrial waste upcycling businesses.